2004
DOI: 10.1152/ajpgi.00499.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Cancer I. Rodent models of infectious gastrointestinal and liver cancer

Abstract: Chronic gastrointestinal and liver infections account for a significant percentage of human cancer deaths. Rodent models help elucidate how infection can lead to malignancy. Helicobacter pylori, the leading cause of human gastric tumors, produces similar disease in Mongolian gerbils. H. pylori, H. felis, and H. hepaticus induce stomach, lower bowel, or liver tumors in susceptible wild-type and genetically engineered mice. Immune dysregulated mice recapitulate features of inflammatory bowel disease including co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 20 publications
2
101
0
Order By: Relevance
“…The combination of these effects could be beneficial for cell survival in the early phase of the infection. The sustained overproduction of IL-6 and anti-apoptotic proteins Bcl-2 and Bcl-XL facilitates proliferation of the inflamed cells, thereby promoting the development of pre-malignant dysplastic lesions that ultimately give rise to cancer (47,48). In the ceca of H.japonicum infected mice, the γ-H2AX staining, the marker for DNA DSBs, was significantly increased when compared with control ceca.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these effects could be beneficial for cell survival in the early phase of the infection. The sustained overproduction of IL-6 and anti-apoptotic proteins Bcl-2 and Bcl-XL facilitates proliferation of the inflamed cells, thereby promoting the development of pre-malignant dysplastic lesions that ultimately give rise to cancer (47,48). In the ceca of H.japonicum infected mice, the γ-H2AX staining, the marker for DNA DSBs, was significantly increased when compared with control ceca.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cao et al 23 reported that antimicrobial therapy induces apoptosis and inhibits proliferation in H. pylori-infected gerbil gastric mucosa. However, the effect of H. pylori eradication on pre-malignant (eg, dysplasia) and malignant histological lesions was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…17 Long-term (41 year) H. pylori infection of Mongolian gerbils can lead to gastric adenocarcinoma, without the coadministration of carcinogens, and gastric cancer in this model occurs in the distal stomach, as in humans. [18][19][20] However, before 2005, the development of gastric cancer in gerbils had never been demonstrated outside east Asia, which limited the widespread use of this model.…”
mentioning
confidence: 87%
“…However, the primary habitat of H. hepaticus is the intestinal tract and the bacterium is linked to inflammatory bowl disease in immunocompromised mice. Recent studies showed that H. hepaticus infected mice might serve as an ideal animal model to study inflammation related carcinogenesis in humans [2,3]. The annotated genome sequence of H. hepaticus has been published [4].…”
Section: Introductionmentioning
confidence: 99%